Perkembangan Sosial dan Emosional Anak Usia Dini - Nurhasanah Nurhasanah; Suci Lia Sari; Nova Adi Kurniawan (STAI Auliaurrasyidin Tembilahan, 2021)
The undeveloped social and emotion of early childhood, especially group B students of Kindergarten As-Salam Pekan Arba Tembilahan takes a serious teachers intention since it is one of many success factors in the future. There needs an extra-efforts to develop from teachers. This research is to discover the teachers’ efforts and factors that follow the development of social-emotional of group B students of TK As-Salam Pekan Arba Tembilahan. This is qualitative descriptive research. The data were collected over interviews, observation, and documentation. The data analyzing technique was triangulation data. The findings showed that the teacher already did many efforts to develop the students’ social and emotions, such as (1) putting attention to them, (2) introducing positive and negative, and its impact on storytelling, (3) giving a comfort zone, (4) practicing positive attitude in the school, (5) reinforcing students by giving salutations and rewards, (6) giving facilities to choose and actualize their hobby, and (7) doing communication between teacher and students.